EVOLUSI PASAR MENURUT PEMIKIRAN IMAM AL GHAZALI - Dwi Cahyono Kuntoro (Misykat al-Anwar Jurnal Kajian Islam dan Masyarakat, 2019)
Al-Ghazali in developing the economy especially in the problem of market evolution departs from the principles of ketauhidan, akhirat, and minutes. From this principle developed multidimensional economic goals. Not only aimed at material-oriented but also in order to achieve spiritual satisfaction. In detail described al-Ghazali that the creation of the evolution of the market, namely "Can farmers live where agricultural equipment is not available.In contrast blacksmiths and carpenters live where agricultural land does not exist, but naturally they will meet each other's needs In the context of the method of mining of economics, Al-Ghazali offers an inductive method, which is based on the Qur'an and al-Hadith and based on the phenomena of the reality of economic activity, and the value surrounding it The method used in this paper is literary research that reads and examines the various sources related to the topic Conclusion Al-Ghazali's economic thinking is a voluntary exchange and market evolution that includes demand, supply, price, profit and market ethics as well as usury and the role of the state in the advancement of the public economy. Thus, in the perspective of Islamic law it can be concluded that al-Ghazali's thought of market evolution is not contrary to Islamic law (law in the field of muamalah)